Study of strengthening 21st-century skills in prospective science teacher based on gender - Rian Vebrianto; Ridzwan Bin Che Rus; Misbahul Jannah; Zelly Putriani; Alaniyah Syafaren (JURNAL BIOEDUKATIKA, 2020)
21st-century skills are important for teachers. Pre-service teachers have to have the competence needed in the 21st Century to teach these 21st-century skills to their students in the future. This purposes of the study are the strengthening of the 21st Century Skills of pre-service teachers of science in three campuses, namely Sultan Syarif Kasim State Islamic University, Sultan Idris Malaysia University of Education, and Ar Raniry State Islamic University in Banda Aceh and to determine the correlation of 21st-century skills-based on gender. This study employed quantitative design using a survey research method. The instrument used for this study was the questionnaire of 21st century skills. The questionnaire for the 21st century skills are 30 items to represent the five constructs (Digital Age Literacy, Inventive Thinking, Effective Communication, High Productivity and Values and Spirituality) with the reliability index of the instrument was 0.84. This study was conducted on 250 pre-service teachers consisting of 46 male gender and 204 female gender from three campuses. The results showed that teachers of science had good reinforcement of The 21st Century Skills. While based on data analysis, the correlation between male and female gender is weak but has the same relationship to strengthening the 21st Century skills.